Tablet or Notebook? A Comparative study of Student’s Perception of Different Technological Approaches in Computer Supported Chemistry Labs - Skoršepa, Marek; Kmeťová, Jarmila; Horváthová, Erika (Scientia in educatione, 2020)
School experimenting assisted by computer devices has been reported as one of promising ways of learning science for a couple of decades. However, technology has been changing very often and quickly. This is why many technological approaches can be seen in the field of computer assisted laboratory work over the years. This paper deals with the comparison of student’s perception of experimenting with measuring systems using two different computer terminals: (i) notebooks and (ii) tablets. For the purpose of the study we designed a set of four computer-based laboratory activities for chemistry to be performed by two cohorts of Slovak grammar school students. While working on the same activities and with the same measuring system, one cohort operated measuring systems connected to notebooks and the other one operated measuring systems connected to tablets. The goal of the study is to find out whether different technological approaches are able to generate significant differences in students’ perceptions of such a type of experimenting.